Phytochemical Screening and Antimicrobial Activity of the Leaf Extract of Mirabilis jalapa Against Pathogenic Microorganisms - V. Kiran Kumar,; N. Ravi Sankar,; S. Ramya,; R.V. Sahaja,; K. Saritha,; K. Govinda Reddy,; N. V. Naidu, (International Journal of Phytomedicine, 2010)
Investigation of the phytochemical constituents and antimicrobial activity of the leaf extracts of Mirabilis jalapa were carried out using acetone, chloroform, ethanol and methanol. These extracts were subjected to screening of preliminary phytochemical tests. Phytochemical analysis showed the presence of alkaloids, flavanoids, phenols, glycosides, tannins, saponins and lignins. The methanol extract exhibited the largest zone of inhibition (21mm in dia with 500µg/disc extract) against Staphylococcus aureus and the highest inhibition of fungal radial mycelial growth (97.5% with 500µg/ml medium) against Aspergillus flavus. The methanol extract exhibited the lowest MIC against Staphylococcus aureus (39 µg/ml) and Aspergillus flavus (45µg/ml). It appeared that M. jalapa could be a potential natural source of new antimicrobial agent.